ANALISIS METODE BAYESIAN PADA SISTEM ANTREAN PELAYANAN LOKET TIKET STASIUN TAWANG SEMARANG - Aurum Anisa Salsabela; Sugito Sugito; Budi Warsito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2021)
Jamming is one of the serious problem in Indonesia caused by the increase of vehicle. The government has made solution for this situation for example was public transportation. Train is one of the suitable public transportation because of the ticket price was cheap. Tawang Railway Stasion Semarang was the biggest railway station in Semarang. In the specific day such long holiday or celebrating day, many people have chosen train to bring them. This make a queuing situation on the counter of station. Queue theory models provide the random of arrival and service time. The Bayesian theory suits to handle the problem of queuing that has been working for several times. Based on the analysis of the queue models for customer service, self-print tickets, cancellation and ordering are (G/G/c):(GD/∞/∞) from the posterior distribution with combination from prior distribution and likelihood sample. The combination of prior distribution and likelihood sample used in this research is Poisson distribution for all ticket counter except the arrival for cancellation counter which Normal distribution. The likelihood sample used Poissonn distribution for all ticket counter, except for self-print tickets which Diskrit Uniform Distribution. Queue models can be used to count the size of the system performance. Based on the calculations and analysis, it can be concluded that the queueing system to the customer service, self-print tickets, cancellation and ordering have been good because its steady state and busy probability is higher than jobless probability. Keywords: Tawang Railway Station, Queue, Bayesian, size of the system performance